The Mobilizing School Programme and its Implications for Students' School Well-Being in Primary Schools - Zulfikri Zulfikri; Arita Marini; Linda Zakiah (Universitas Muhammadiyah Enrekang, 2024)
The focus of the problems in this study are: (1) a general description of driving school and school well-being; (2) the implication of driving school programme to students' school well-being in primary school. This research uses a literature study method. The literature study research method is a research method by reading and analyzing readings related to the theme taken. The results of the study describe the intervention of the Driving School Program: (a) Consultative and Asymmetric Assistance, (b) Strengthening Human Resources in Schools, (c) Learning with New Paradigms, (d) Data-Based Planning, and (e) School Digitalisation. The driving school programme focuses on developing holistic student learning outcomes by realizing the Pancasila Student Profile which includes cognitive (literacy and numeracy) and non-cognitive (character) competencies. The intervention and focus of the driving school to realize the Pancasila learner profile has positive implications on aspects of school well-being, namely: (a) School conditions (Having) include things such as a safe physical environment, comfort, noise, ventilation, air temperature, (b) Social Relationships (Loving) social learning environment, student-teacher relationships, relationships with schoolmates, group dynamics, bullying, the relationship between home and school, decision-making at school, and the atmosphere throughout the school organization, (c) Health Status (health) is divided into the components of physical and mental illness, and Self-fulfilment (Being) This opportunity can be equal opportunities for all students to be part of the school community and make decisions about their existence at school.